The Hermeneutic Interpretation of Ta'lim Mutaallim By Al-Zarnuji In Shaping The Morals of Santri at Pesantren - Maslani Maslani; Ratu Suntiah; Karman Karman; Nursaid Nursaid (Nazhruna: Jurnal Pendidikan Islam, 2026)
Islamic moral education has long been positioned as a normative and prescriptive process that emphasizes the doctrinal transmission of values. Such an approach tends to overlook the interpretive dimension and learners’ lived experiences in the process of internalizing moral values. Departing from these limitations, this article examines Ta‘lim al-Muta‘allim by al-Zarnuji as a form of lived moral pedagogy within the pesantren context, employing Paul Ricoeur’s hermeneutic theory of mimesis as the analytical framework. The purpose of this study is to understand how the moral teachings contained in Ta‘lim al-Muta‘allim are not merely taught as normative texts but are internalized, mediated, and dynamically interpreted by educational actors in the pesantren. This research adopts a qualitative case study design conducted at Pesantren Buntet, Indonesia. Data collection techniques include participant observation, in-depth interviews with kiai, ustaz, and santri, and textual analysis of Ta‘lim al-Muta‘allim. The data are analyzed through Ricoeur’s three-stage mimesis framework: prefiguration, configuration, and refiguration. The findings reveal that al-Zarnuji’s moral principles function as pre-reflective ethical horizons that shape the dispositions of santri (Mimesis I), are configured into coherent pedagogical narratives through the authority and exemplarity of the kiai (Mimesis II), and are actively refigured by learners in their responses to contemporary educational challenges (Mimesis III). The implications of this study underscore that Islamic moral education should be understood as a hermeneutic-narrative praxis that integrates textual authority, pedagogical mediation, and learner agency, thereby contributing to the development of character education discourse in the modern era.